DETERMINATION OF NITRATE AND NITRITE CONCENTRATION OF SOME BOTTLED DRINKING WATER BRANDS IN HAWLER CITY KURDISTAN REGION, IRAQ - Tablo Abdulrahim Ahmed (Journal CleanWAS, 2024)
This investigation was done to find out how much packaged natural spring and mineral water consumed in Hawler City contained nitrate (NO3-) and nitrite (NO2-). Between January and March of 2021, a total of sixty water samples with four replications from fifteen different companies (Life, Mazi, Reni, Lava, Kani, Rovian, Rawan, Hayat, Vauban, Grand Barbier, Evian, Bakoor, Shexy balak, Mira, and Tiyan) were tested for nitrate and nitrite. Using the spectrophotometric method, the levels of nitrate and nitrite were determined. Based on the findings, every water sample contained both nitrate and nitrite. The findings indicated that the average concentrations of nitrate and nitrite in the water sample ranged from 1.6 mg/l to 28.48 mg/l and 0.044 mg/l to 0.69 mg/l, respectively. Ultimately, the levels of nitrate and nitrite in a total of 60 water samples from Hawler City were deemed safe for consumption and in compliance with relevant international and national regulations.